Characterization of Eleanor Oliphant in Eleanor Oliphant is Completely Fine by Gail Honeyman: A Study of Transitivity using Corpus-Based Linguistics - Sintia Mulia Rahmadanty; Agus Subianto (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2021)
The application of transitivity system in analyzing characterization, which is an important element in narrative discourse, is addressed in this study. The writer aims to analyze the lexicons that appear to be able to determine the characterization of the character through the Halliday’s transitivity system theory. The data were taken from the novel “Eleanor Oliphant Is Completely Fine” by Gail Honeyman. To obtain the data, the writer used the non-participant observation and documentation method. The data that were taken from narrator discourses and conversations based on Eleanor Oliphant as an active participant, were annotated manually and processed with the help of the corpus linguistics. The results show that there are six transitivity processes found, which are: material, mental, relational, behavioral, verbal, and existential processes and seventeen circumstances. Each process has lexicons that frequently occur, such as work, drink, read, think, thought, remembered, felt, decided, smiled, laugh, said, stood, and sit. The lexicons can show the characterization of the Eleanor representing her appearance, trait, behavior, identity, and psychology. This can be concluded that the transitivity system can be used to analyze the characterization of Eleanor, who is a hard worker and a drinker who has a trauma and clinical depression, but she tries to live a better life in the present.Keywords: characterization; Eleanor Oliphant; transitivity system; corpus linguistics; lexicon